2017
DOI: 10.1111/joa.12713
|View full text |Cite
|
Sign up to set email alerts
|

Development and maturation of the fibrous components of the arterial roots in the mouse heart

Abstract: The arterial roots are important transitional regions of the heart, connecting the intrapericardial components of the aortic and pulmonary trunks with their ventricular outlets. They house the arterial (semilunar) valves and, in the case of the aorta, are the points of coronary arterial attachment. Moreover, because of the semilunar attachments of the valve leaflets, the arterial roots span the anatomic ventriculo‐arterial junction. By virtue of this arrangement, the interleaflet triangles, despite being fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 30 publications
2
34
0
Order By: Relevance
“…In particular, NCCs expressing Krox20 contribute to the insertion zone of the valve leaflets and the interleaflet triangle between each leaflet. Consistently, a recent study showed that the interleaflet triangle fibrous tissues derived from the outflow cushions region have contribution from NCCs (Richardson et al, 2017).…”
Section: Discussionsupporting
confidence: 70%
“…In particular, NCCs expressing Krox20 contribute to the insertion zone of the valve leaflets and the interleaflet triangle between each leaflet. Consistently, a recent study showed that the interleaflet triangle fibrous tissues derived from the outflow cushions region have contribution from NCCs (Richardson et al, 2017).…”
Section: Discussionsupporting
confidence: 70%
“…However, at E11.5, prior to expression of CS56, and also at E12.5, Versican was expressed within the bulk of the IC ( Figure 2J–O ). At E10.5 Sox9, a transcription factor necessary for the formation of endocardial cushions and maintained in mature valve leaflets ( Akiyama et al, 2004 ; Richardson et al, 2018 ), was abundantly expressed in the circumferential layer of cardiac jelly where the main cushions form, but only in the area immediately adjacent to the endothelium overlying the IC that was labelled by CS56 ( Figure 2P,S – compare to 2 D,G); there was no Sox9 in the main part of the IC at this stage. At E11.5 Sox9 was also expressed throughout the IC and this was maintained at E12.5 ( Figure 2Q,R,T,U ).…”
Section: Resultsmentioning
confidence: 99%
“…The dorsal pericardial wall and the pharyngeal mesoderm are composed of SHF cells that directly generate the outflow tract myocardium, much of the smooth muscle and fibrous tissue in the proximal and distal outflow vessel walls, and also the endocardium that lines these structures ( Waldo et al, 2005 ; Harmon and Nakano, 2013 ; Verzi et al, 2005 ; Richardson et al, 2018 ). Moreover, the SHF through endothelial EndMT, indirectly populates the outflow tract cushions ( Verzi et al, 2005 ); Figure 3—figure supplement 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aortic and pulmonary valves, which sit within the arterial roots between the myocardium of the left and right ventricular outflow tracts and the aorta and pulmonary trunk, respectively, are structurally similar to one another, and are closely comparable in humans and mice [ 1 , 2 , 3 ]. Thus, in the mature heart both the aortic and pulmonary valves have three superficially similar leaflets that form the moving parts of the valve.…”
Section: Anatomy Histology and Nomenclature Of The Mature Arteriamentioning
confidence: 99%